Analysis of National Standards of Education in the Disruptive Era (Study of Descriptive Analysis at SMA Negeri 53 Jakarta and SMA Negeri 59 Jakarta) - Ujang Cepi Barlian; Fetty Budi Arifani; Bustomi Bustomi; Catur Galuh Ratnagung; Waska Warta (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character, and skills needed by themselves, society, nation and state. National Education Standards in PP 57 of 2021 concerning National Education Standards are the minimum criteria regarding the Education system in all jurisdictions of the Unitary State of the Republic of Indonesia. National education standards are the minimum criteria that must be met in the implementation of education. National Education Standards include Content Standards, Process Standards, Graduate Competency Standards, Educators and Education Personnel Standards, Infrastructure Standards, Management Standards, Financing Standards, Assessment Standards. In order to maintain the quality of education, the consistency of the functions and objectives of education, the curriculum, learning process, and managerial as a whole must refer to and be guided by the National Education Standards. The objectives of this research are (1) to analyze the 8 National Standards of the Disruptive Era at SMA Negeri 53 Jakarta and SMA Negeri 59 Jakarta (2) to provide input based on findings regarding the application of the 8 National Education Standards to improve the quality of education and prepare highly competitive graduates. This study uses a qualitative descriptive research design. This type of research is a descriptive analysis study. The data used is primary data. Data collection techniques used are interviews and documentation.